2015
DOI: 10.12783/issn.2376-578x/12/1/2
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Dilute-acid Hydrolysis (DACH) of Distillers Grains and Ethanol Fermentation

Abstract: Distillers grain (DG) is an abundant and low-cost lignocellulosic biomass. The objective of paper is to compare the influence of different acids on hydrolysis of DG and select the best acid. The results indicate that sulfuric acid is the most effective acid, and the optimum hydrolysis conditions are temperature 100°C, sulfuric acid concentration 2.0%, solid-liquid rate 1:12 (w/v), time 3.0 h. Under these conditions, the concentration of reducing sugar (RS) and xylose are 43.69 g/L and 35.16 g/L, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…Thus, an increase in the temperature will increase the hydrolytic rate. This finding agreed well with a study conducted by Ren et al, [13] which reported an increase in the glucose yield with the temperature for the hydrolysis of distiller grains.…”
Section: Resultssupporting
confidence: 93%
“…Thus, an increase in the temperature will increase the hydrolytic rate. This finding agreed well with a study conducted by Ren et al, [13] which reported an increase in the glucose yield with the temperature for the hydrolysis of distiller grains.…”
Section: Resultssupporting
confidence: 93%